2019
DOI: 10.1159/000499672
|View full text |Cite
|
Sign up to set email alerts
|

A Four-Factor Model of Work Addiction: The Development of the Work Addiction Risk Test Revised

Abstract: Background: Work has a crucial role in individuals’ productivity, social life, and psychological well-being. Despite various definitions of work addiction in the literature, the number of psychometrically reliable instruments is limited. Objectives: The aim of this study was to psychometrically test and revise the factor structure of the Work Addiction Risk Test (WART), one of the most widely used instruments assessing work addiction. Method: The full version of the WART [Robinson, Post, & Khakee, 1992] was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 45 publications
(77 reference statements)
0
21
0
Order By: Relevance
“…The risk of work addiction was assessed using the Work Addiction Risk Test Revised [ 7 ]. The original 25-item scale was developed by Robinson, Khakee, and Post [ 65 ], but the present study utilized the 17-item shortened version because it has better psychometric properties [ 7 ]. Individuals rate themselves on a four-point Likert scale from “never” to “always”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of work addiction was assessed using the Work Addiction Risk Test Revised [ 7 ]. The original 25-item scale was developed by Robinson, Khakee, and Post [ 65 ], but the present study utilized the 17-item shortened version because it has better psychometric properties [ 7 ]. Individuals rate themselves on a four-point Likert scale from “never” to “always”.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, work addiction and related overwork can have several adverse physical, mental, and social consequences both for individuals and their environment [ 4 , 5 ]. Although the prevalence of work addiction varies across surveys due to the different definitions, methods, and screening instruments used, largescale representative studies have shown that the lifetime prevalence of work addiction was 8.3% among Norwegian workers [ 6 ], and 8–9% among Hungarian employees [ 7 , 8 ]. Due to its seemingly high prevalence compared to other addictive behaviors [ 9 ], there is an increasing interest in understanding the psychosocial correlates of work addiction [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades many researchers have world-wide tried to develop measures of workaholism, as it was recognized as a harmful disease (Andreassen et al, 2018;Griffiths et al, 2018;Urbán et al, 2019). Two American measures, WorkBAT by Spence and Robbins (1992) and the WART by Robinson (1998Robinson ( /2013, have been widely used in assessing workaholism prevalence.…”
Section: Psychometric Properties Of K-waq and Its Validitymentioning
confidence: 99%
“…We were able to identify a total of 33 independent studies that investigated the factor structure and reliability of the UWES-9 (more details are provided in Supplementary Table 1 1 We carried out this study in Hungary which provided us with a unique context for multiple reasons. First, recent national surveys show that Hungarian people spend a lot of time with work, around 43-44 hours per week (Kun et al, 2020;Urbán et al, 2019). Second, at the same time, Hungarian employees are substantially less engaged with their work when compared to other European countries (Schaufeli, 2018).…”
Section: The Dimensionality Of Work Engagementmentioning
confidence: 99%